PENINGKATAN PENDAPATAN ASLI DESA (PADES) DESA RANTAU SAKTI MELALUI UNIT USAHA BUMDES SUMBER REJEKI - Muhammad Amri Yunal (Jurnal Ilmiah Cano Ekonomos, 2023)
There are many efforts that can be made by the village government to improve the village economy for the prosperity of the village community. One of these efforts is to establish Village Owned Enterprises (BUMDes). One of these efforts is to establish Village Owned Enterprises (BUMDes). In line with the purpose of establishing BUMDes listed in the Regulation of the Minister of Villages, Development of Disadvantaged Regions, and Transmigration number 4 of 2015 is to increase Village Original Income (PADes). The purpose of this study was to determine the increase in Village Original Income (PADes) in Rantau Sakti Village through the Sumber Rejeki BUMDes business unit. The research approach used in this study is a qualitative research with a descriptive type. The primary data sources are the village head, BUMDes director and BUMDes secretary. While secondary data include: data in the form of reports, documents, raw data and necessary data. Data collection instruments used in this study were observation, interviews and documentation studies. The data analysis method used in this research collects data, reduces data, presents data and draws conclusions. The results showed that Village Original Income (PADes) for Rantau Sakti Village continued to experience a significant increase of 27% from 2019 to 2022. The Sumber Rejeki BUMDes business unit that contributed quite a lot was the savings and loan business unit which has been managed since 2019